THU0066 Circulating mirnas as potential biomarkers of disease and cardiovascular risk in rheumatoid arthritis patients. (12th June 2018) - López-Pedrera, C.; Barbarroja, N.; Ruiz-Limón, P.; Remuzgo-Martínez, S.; Arias de la Rosa, I.; Ábalos-Aguilera, M.C.; Jimenez-Gomez, Y.; Ortega, R.; Collantes, E.; Escudero, A.; Lopez-Mejías, R.; Gonzalez-Gay, M.A.; et al.
Abstract : Background: Circulating miRNAs have been proposed as attractive candidates as both diagnostic and prognostic biomarkers in various diseases, including a spectrum of autoimmune and cardiovascular conditions. Yet, the contribution of circulating miRNAs to the cardiovascular pathogenesis of Rheumatoid Arthitis (RA) patients and their potential role as biomarkers are still unknown. Objectives: To identify circulating miRNAs as potential biomarkers of disease features and cardiovascular (CV) risk in RA. Methods: Plasma samples of 48 healthy donors (HDs) and 124 RA patients were collected. In the discovery phase, an array of 2083 human miRNAs was performed by using HTG EdgeSeq miRNA Whole Transcriptome Assay (Next generation sequencing) in 9 plasma samples (3 HDs, and 6 RA patients). Then, differentially expressed miRNAs, were selected and validated by RT-PCR in the whole cohort of patients and HDs. Potential targets of the validated miRNAs were identified by using Ingenuity Pathway Analysis (IPA) software and analysed at protein levels (Multiplex Assay). Correlation and association studies of altered miRNAs with analytical and clinical variables were also performed. Results: The miRNA whole Transcriptome assay showed that 360 miRNAs were differentially expressed in RA patients in relation to HDs, including 261 upregulated and 97 downregulated. Functional classification (IPA) demonstrated that deregulated miRNAs were mainly involved in processes such as inflammatory response, connective tissue development and function, haematological disease, tissue development, and immunological disease. Nine microRNAs, selected among the most differentially expressed in the array, were selected for validation in all the subjects recruited (miR-299, miR-567, miR-4293, miR-135b, miR-6816, miR-346, miR-143, miR-199a, miR-106a, miR-148b). In silico analyses showed that these miRNAs had potential targets related to cytokine signalling, atherosclerosis pathway and intracellular signalling. The altered levels of selected miRNAs and its putative target proteins were validated in the whole cohort of patients. A number of serum miRNAs in all the RA patients analysed were found inter-related and associated to autoimmunity (positivity for anti-CCPs and RF), bone erosion, inflammation (CRP, ESR, TNFa, IL6, IL8, IFN and IL-2), and evolution time. We could further identify a specific signature of four miRNAs (miR143, miR106, miR148b and miR567) that identified RA patients that had suffered previous CV events and specifically associated with the increase in the carotid intima-media thickness (CIMT) and with 'Framingham CV risk factors' such as diabetes, obesity or dyslipidemia. Conclusions: We have branded novel and specific circulating miRNAs related to disease features and CV risk in RA patients, including, their autoimmune and inflammatory profile, the presence of Framingham risk factors and incipient atherosclerosis. These circulating miRNAs might be thus considered useful tools for the management of the disease in this autoimmune condition. Acknowledgements: Funded by JA (CTS-7940) and the Ministry of Health (ISCIII, PI15/01333 and RIER RD16/0012/0015) cofinanced with FEDER funds. Disclosure of Interest: None declared